A case of lymphogranuloma venereum of 20 years' duration. Isolation of Chlamydia trachomatis from perianal lesions. Issue 5 (October 1980) - Dan, M; Rotmensch, H H; Eylan, E; Rubinstein, A; Ginsberg, R; Liron, M
Abstract : Chlamydia trachomatis was isolated from perianal lesions in a patient in whom lymphogranuloma venereum had been diagnosed 20 years previously. Treatment with tetracycline resulted in a pronounced improvement. Although C trachomatis is known to persist for a long time in the host, isolation of the micro-organism from infected tissues after such a prolonged period has not previously been reported.